THE EFFECT OF WORKLOAD, WORK STRESS AND OCCUPATIONAL HEALTH AND SAFETY (K3) ON EMPLOYEE PERFORMANCE OF PT. WANAKARYA MULYA KAHURIPAN OKU TIMUR - Sahabuddin, Romansyah (PUSAT KEWIRAUSAHAAN UNIVERSITAS BALIKPAPAN, 2024)
This study aims to determine [1] the effect of workload, work stress and occupational health and safety (K3) on employee performance [2] the effect of employee workload on employee performance [3] the effect of work stress on employee performance [4] the effect of occupational health and safety (K3) on employee performance PT. Wanakarya Mulya Kahuripan This study is an associative type with the variables used are Workload, Work Stress, Occupational Health and Safety (K3) and employee performance, the sample used is 98 employees using simple random sampling. The data used are primary and secondary data. Data collection methods using questionnaires. Data processing techniques using multiple linear regression analysis, F test, t test and coefficient of determination. The results of the study based on multiple linear regression indicate that there is an Effect of Workload, Work Stress and Occupational Health and Safety on Employee Performance at PT. Wanakarya Mulya Kahuripan. The results of the t test indicate that there is an Effect of Workload, Work Stress and Occupational Health and Safety (K3) on Employee Performance at PT. Wanakarya Mulya Kahuripan OKU Timur. The results of the determination coefficient show that the variables Workload, Work Stress and Occupational Health and Safety (K3) are able to contribute to the increase and decrease in Employee Performance by 47.7%. While the remaining 52.3% is influenced by other factors outside this study.